An Intersectional Multicultural Approach to Advising and Counseling Transborder Mexican‐American Men in the Community College. Issue 164 (1st November 2018) - Falcón Orta, Vannessa; Harris, Frank; Leal, Ulises; Vasquez, Marissa
Abstract: The purpose of this chapter is to propose multicultural gender‐aware counseling practices from an intersectionality perspective to advising Mexican‐American men in the community college who live a transborder lifestyle in the San Diego–Tijuana region.